A systematic approach to find the best road map for enhancement of a power plant with dew point inlet air pre-cooling of the air compressor. (15th October 2017) - Sohani, Ali; Farasati, Yashar; Sayyaadi, Hoseyn
Highlights: Dew-point cooler was proposed in order to enhance a power plant. A systematic method to find the best road map was offered. Investigation was done considering four optimization scenarios and different investment plans. Payback period of the final plan was 2.67 years. Annual net power and steam generation's capability were improved 6.02% and 8.92%. Abstract: Dimensional characteristics and operating parameters of the optimized Maisotsenko indirect evaporative cooler for pre-cooling of the compressor's inlet air and consequently enhancement of the gas-turbine power generation system as well as the best investment strategy for it were found for an in-operation combined cycle power plant through a systematic approach. Four optimization scenarios were proposed considering different combinations of annual average of net power of the gas-turbine power generation system, payback period time and enthalpy difference of exhaust gases compared to the reference state of each gas-turbine power generation system as objective functions. In each scenario, optimization was conducted for different possible percentages of investment allocated to the research and development of the project. After that, analytical hierarchy process was used to find the best percentage of investment allocated to the research and development of the project of each scenario and the final selected one. Having introduced the approach, it was implemented for Montazer-Ghaem combined cycle power plant in Iran. The results showed for that case study, the analytical hierarchy process selected an optimization scenario in which the annual average of the net power and the enthalpy difference of the exhaust gases compared to the reference state were the objective functions and 15% of the total profit of the gas-turbine power generation system sold electricity was dedicated to the improvement project. This optimization had the payback period time of 2.67 years and it also improved the annual average of the net power of gas-turbine power generation system and enthalpy difference of the exhaust gases compared to the reference state 6.02 and 8.92%, respectively.